Meningkatkan Mutu Belajar Fiqih melalui Model CTL Berbasis Canva: Studi Efektivitas di Madrasah Tsanawiyah - Al Ghozali, M. Dzikrul Hakim; Azizah, Nur Mita Riski (YASIN, 2025)
The learning process in fiqh subjects at MTs Sunan Gunung Jati Jombang still relies on conventional models, and the integration of digital media remains suboptimal, leading to less-than-optimal student learning outcomes. This study aims to analyze the effectiveness of the Canva-based Contextual Teaching and Learning (CTL) model in enhancing the quality of fiqh learning. The research employs a pre-experimental design with a one-group pretest-posttest approach, where a single group undergoes both pre-test and post-test assessments. The sample consists of 20 students selected through a saturated sampling technique. Data collection methods include tests/questionnaires, observation, and documentation, with data analysis conducted using IBM SPSS Statistics Software. The results of the N-Gain test indicate that the effectiveness of the Canva-based CTL model is 57.536%, which falls within the "moderately effective" category. This suggests that while the Canva-based CTL model contributes positively to improving students' learning quality in fiqh subjects, further refinement may be needed to enhance its impact. The findings highlight the potential of digital learning media in Islamic education and emphasize the need for innovative pedagogical approaches to optimize student engagement and learning outcomes. Future research should explore additional variables that may influence the effectiveness of digital learning models and consider comparative studies with other instructional methods to provide a more comprehensive understanding of their pedagogical implications.